Hegel and Canada : unity of opposites? - Dodd, Susan, 1966-; Robertson, Neil G. (University of Toronto Press, 2018)
Hegel and Canada is a collection of essays that analyses the real, but under-recognized, role Hegel has played in the intellectual and political development of Canada. The volume focuses on the generation of Canadian scholars who emerged after World War Two: James Doull, Emil Fackenheim, George Grant, Henry S. Harris, and Charles Taylor.